Rationalizing Capitalist Democracy the Cold War Origins of Rational Choice Liberalism - Amadae, S.M. (London University of Chicago Press, 2003)
In Rationalizing Capitalist Democracy, S. M. Amadae tells the remarkable story of how rational choice theory rose from obscurity to become the intellectual bulwark of capitalist democracy. Amadae roots Rationalizing Capitalist Democracy in the turbulent post-World War II era, showing how rational choice theory grew out of the RAND Corporation's efforts to develop a "science" of military and policy decisionmaking. But while the first generation of rational choice theorists?William Riker, Kenneth Arrow, and James Buchanan?were committed to constructing a "scientific" approach to social science research, they were also deeply committed to defending American democracy from its Marxist critics. Amadae reveals not only how the ideological battles of the Cold War shaped their ideas but also how those ideas may today be undermining the very notion of individual liberty they were created to defend.
Includes index
Keywords: Rational Choice theory